Writing Fieldwork Assignment Reports - Pant, Prem R. (Journal of Nepalese Business Studies, 2006)
This paper has been prepared with an objective to provide the guidelines to the BBS students to write the fieldwork report and teachers to guide their students in writing the fieldwork report. So, this paper has included formats of fieldwork report (both in English and Nepali) as prescribed by Office of the Dean, Faculty of Management, Tribhuvan University and procedures to be followed in preparing the report.Journal of Nepalese Business Studies Vol.1(1) 2004 pp.38-52